Pengoptimalan Produksi pada Pembuatan Rak Piring Berdasarkan Studi Waktu Kerja - Fahmi, Izudien; Putri, Erni Puspanantasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
UD Yurike, a furniture company in Surabaya, the production process in this company is constrained by the absence of a standard time to complete one unit of plate rack. This led to the absence of a target number of units to be completed by each worker per day. This condition has an impact on the difficulty of achieving targets in the midst of fluctuating demand and the manual assembly process. The purpose of this research is to understand the standard time to complete one unit of plate rack and the labor requirements per division using the Stopwatch Time Study method. The results of data processing show that the amount of standard time needed to complete one unit of plate rack is 1967.11 seconds (equivalent to 32.79 minutes), with additional labor requirements for the pipe frame coloring division to 2 workers and wire frame coloring to 4 workers and other.